Content Gap Analysis in Digital Marketing Communication Strategy of Jember Batik SMEs Examining Expectation and Reality Differences - Izzuddin, Ahmad; Setianingsih, Wahyu Eko (Yayasan Sinergi Kawula Muda, 2026)
This study examines the content gap in the digital marketing communication strategies of batik SMEs in Jember by highlighting the discrepancy between consumer expectations and the perceived reality of digital content, as well as analyzing their influence on consumer engagement. The novelty of this research lies in the integration of expectation–reality gap analysis with a mixed-method approach that combines consumer survey data and qualitative insights from SME owners within a cultural industry context that has rarely been explored simultaneously. The study employs a mixed-method design using SEM-PLS analysis of 100 consumer respondents and in-depth interviews with three batik SME owners, where quantitative data were collected through a six-point Likert scale questionnaire and qualitative data were analyzed using thematic analysis to explain and strengthen the structural findings. The results indicate that both consumer expectations and perceived content reality significantly influence consumer engagement, with perceived content reality, particularly authenticity, emerging as the most dominant factor, while the structural model demonstrates strong explanatory and predictive power. Qualitative findings reveal that digital content practices remain largely reactive, characterized by limited planning, insufficient human resources, and a strong emphasis on product-oriented promotion, which contributes to the persistence of the content gap between audience expectations and delivered content. Therefore, this study concludes that aligning consumer expectations with authentic, structured, and culturally driven digital content is essential to enhance engagement, implying that batik SMEs must strengthen strategic content planning while maintaining authenticity to improve their digital competitiveness.